2009
DOI: 10.1002/jcb.22102
|View full text |Cite
|
Sign up to set email alerts
|

PI3K Acts in synergy with loss of PKC to elicit apoptosis via the UPR

Abstract: It is known that Ras mutations, together with loss of PKC, are apoptotic in various types of mammalian cells. The mechanism of how aberrant Ras transmits this apoptotic signaling remains unclear. Using three V12-Ha-ras loop mutants that preferentially bind to and activate one of Ras effectors, we tested the role of Ras downstream pathways in the induction of apoptosis in rat lung epithelia, human lung or prostate cancer cells. After PKC inhibition, the activation of PI3K/Akt renders the susceptibility of cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…The addition of GO6976 (a potential PKC α and β inhibitor) induced various types of cells expressing an active ras to undergo apoptosis (Guo et al ., 2009). The suppression of PKC α by a kinase dead PKCα mutant was also reported to render salivary epithelial cells the susceptibility to PKC δ-dependent apoptosis (Matassa et al 2003).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The addition of GO6976 (a potential PKC α and β inhibitor) induced various types of cells expressing an active ras to undergo apoptosis (Guo et al ., 2009). The suppression of PKC α by a kinase dead PKCα mutant was also reported to render salivary epithelial cells the susceptibility to PKC δ-dependent apoptosis (Matassa et al 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The inhibition of PKC α was able to induce apoptosis through eliciting oxidative or ER stress in cells (Reylan et al ., 2007). We previously showed that the suppression of PKC by GO6976 (a potential PKC α and β inhibitor) triggers apoptosis through Akt-mediated ER stress (Guo et al 2009). GO6976 was shown to affect the activity of other types of serine/threonine kinases (for example, Chk1) (Aaltonen et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The blockade of PKC α sensitized salivary epithelial cells to PKC δ–induced apoptosis, in which JNK was required 40. Recently, we demonstrated that the concurrent suppression of PKC α/β conferred cells expressing oncogenic ras or Akt the susceptibility to apoptosis, via upregulating PKC δ 41. Our current study again demonstrated that in the presence of aberrant Ras signaling, loss of PKC δ causes the increase of PKC α/β expression and activation of JNK, resulting in apoptosis.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, targeting oncogenic Ras is a very attractive strategy for the development of new anticancer therapies. Studies have highlighted the respective roles of Ras in the induction of apoptosis 41,43-45. High-throughput RNA interference screens identified various kinases that are essential for tumor cells harboring mutated K-ras to survive 32,33.…”
Section: Discussionmentioning
confidence: 99%